Eight and a Half Syndrome: A Rare Case of Pontine Infarction - Kowsalya, Akkayasamy; Thanemozhi DO, Srinivasan (Nepalese Journal of Ophthalmology, 2021)
Introduction: This case report describes “one-and-a-half” syndrome with supranuclear facial palsy.Case: 39 years old male hypertensive patient presented with right facial nerve palsy, internuclear ophthalmoplegia and conjugate gaze palsy. Neuroimaging showed acute posterior pontine infarct at medial longitudinal fasciculus, paramedian pontine  reticular formation, abducens nerve nucleus and seventh nerve fascicular zone.Observation: “One-and-a-half”syndrome is characterized by a lateral gaze palsy in one direction and internuclear ophthalmoplegia in the other. Our patient had Right sided one and a half syndrome along with the right facial nerve palsy.  Conclusion: Eight and a half syndrome is a rare manifestation of pontine infarction.